Ius Contituedum Regulation of the Substance of Police Repressive Actions in Protests that Result in Riots - Ryan Sukma Wibawa; Fence M. Wantu; Dian Ekawty Ismail (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The purpose of the study was to analyze the legality and limits of police repressive actions against protests that resulted in riots. This type of research is normative legal research with a legislative approach, a case approach and a conceptual approach. The analysis used in this study is an analytical descriptive technique. The results of the research show that the law is always used as a guideline in limiting all citizens' behavior to stay on the right path. Protests often lead to riots, destruction of public facilities, attacks on officers, and violations of public order, so that there is a criminal threat for protesters who do not maintain order and security. The regulation of police repressive actions in protests that result in chaos still needs special refinement in the context of protests, among which the substance of repressive actions must also harmonize technological developments and digitalization in security maintenance. The rules need to be updated by adding objective indicators of threats, public accountability mechanisms, transparent documentation obligations, measurable proportionality standards, and room for recovery for victims of abuse of power.